Golden-C: mango drink enriched with antioxidants of mas cotek / Hasseri Halim … [et al.] - Halim, Hasseri; Mohamad Zahari, Nur Izalin; Ramli, Salfarina; Eshak, Zolkapli (Research Innovation Business Unit, 2014)
Beneficial health effects of dietary antioxidants have prompted the idea of commercial antioxidant-rich beverages. Malaysia has been blessed with a variety of fruits and herbs. Our ancestors have been consuming raw vegetables and herbs as part of their daily diet. Scientific studies have been carried out to evaluate the beneficial effects of Malaysian herbs. A number of studies support the intake of our local herbs to prevent diseases mainly caused by oxidative stress. Today, some of our herbs have been turned into products, for example tablets and some are incorporated into coffee to simplify and assist the pharmacological effects of the herbs. Known to be rich in vitamin C, mango is among the reputable fruit in the world, in addition a number of high-quality mango clones are available in Malaysia. Our interest has been at incorporating herb extract into a mango drink to create a new way of enjoying the goodness of mango with local Malaysian herb. Antioxidant properties of herbs have been proved relevant to the herb’s beneficial effects. Phenolic compounds such as flavonoids have been found responsible for the observed antioxidant effects. Thus, herbs known for high antioxidant properties have been in our interest. However, some herbs are not suitable to be incorporated into the mango drink due to the pungent taste and colour of the herb extract that may interrupt the organoleptic properties of the mango drink. It was found that dried Ficus deltoidea leaves extracted with water at 50 degree celsius for 20 hours yielded aqueous extract with the highest flavonoids and total phenolic content. This traditional herb, known locally as Mas Cotek, is a plant from the family Moraceae and has been used for its medicinal properties. It is used to treat pneumonia, diabetes, hypertension, diarrhoea and gout. A total of 25 flavonoid compounds consisted of 9 flavanols and 16 flavones were tentatively identified from dried leaves of Mas Cotek using high performance liquid chromatography (HPLC) coupled to photodiode array and electrospray ionization mass spectrometry. Mas Cotek could be a suitable candidate to be incorporated with mango drink. Moreover, positive effects of Mas Cotek on glucose and lipid levels and were found safe for use in human. The objective of the present work was to produce a new mango drink enriched with the antioxidants of Mas Cotek (Ficus deltoidea) herb. The bioactive composition (flavonoids and vitamin C) of the drink with Mas Cotek aqueous extract exhibited higher total phenolic content and total flavonoid compound (1386.98 mg/L and 2.9694 mg/L, respectively) compared to mango drink without the incorporation of Mas Cotek which exhibited total phenolic content and total flavonoid compound (1244.55 mg/L and 1.1084 mg/L, respectively). In addition, the Mas Cotek aqueous extract incorporated in the mango drink did not affect the organoleptic properties of the mango drink. Therefore, our study suggested that the Golden-C which is made up of 20% of mango pulp and 50% of Mas Cotek, has the potential to be developed as a new health drink.